How to improve neurodevelopmental and quality of life outcomes following early surgery for congenital heart disease?. (10th September 2013) - Tabbutt, Sarah
<x xml:space="preserve">Abstract</x> This commentary is on the original article by Schaefer et al. on pages 1143–1149 of this issue.